Prescribing Pattern of Granulocyte Colony-stimulating Factor at Tertiary Care Hospital in Riyadh: An Observational Study - Asdaq, Syed Mohammed Basheeruddin (Asian Journal of Pharmaceutics (AJP), 2019)
Background and Aim: Febrile neutropenia (FN) is one of the lethal side effects that necessity hospitalization with fever and life-threatening infections in patients receiving chemotherapy. Several regulatory guidelines recommend the prophylactic use of granulocyte colony-stimulating factor (G-CSF) to overcome this situation. However, rational use of G-CSF is required to avoid economic burden and undesired side effects such as thrombocytopenia. Hence, the current study was designed to evaluate the pattern of G-CSF utilization in our hospital and subsequently assess the appropriateness of its prescription with an estimation on cost factor. Materials and Methods: This is a prospective observational study conducted between December 2017 and February 2018 in the chemotherapy day unit of Prince Sultan Military Medical City, Riyadh, Saudi Arabia, on patients diagnosed with any type of cancer and receiving chemotherapy with G-CSF. The appropriate use of G-CSFs for FN prophylaxis was evaluated based on the American Society for Clinical Oncology (ASCO) guidelines and published data. The demographic, clinical data and G-CSF prescribing data were collected by the clinical pharmacist from patient’s files and the electronic records. The data were analyzed by appropriate statistical tests using SPSS-IBM 23. Results: Of 118 patients who fulfill our inclusion criteria, 26% and 15% of them were breast cancer and colorectal cancer patients, respectively. Based on the ASCO guidelines and published literature, only 42.4% of them were considered appropriate for G-CSF prescription, while 57.6% of them received G-CSF inappropriately. The major reasons for inappropriate prescription were unfamiliarity with chemotherapy regimens or physicians’ anticipated risk of neutropenia in patients receiving chemotherapy. Due to inappropriate prescription, around 61.70% of the cost of G-CSF was wasted. Conclusion: Inadequate knowledge of the chemotherapy risk of FN was documented as major reason for inappropriate prescription of G-CSF. Health-care professionals including clinical pharmacists should play an active to improve G-CSF prescribing pattern. In addition, availability of comprehensive hospital guidelines may rationalize the therapeutic approach in G-CSF prescription.